ATTACHMENT, BORDERLINE PERSONALITY, AND ROMANTIC RELATIONSHIP DYSFUNCTION - Hill, Jonathan (2011)
Previous studies have implicated attachment and disturbances in romantic relationships as important indicators for Borderline Personality Disorder (BPD). The current research extends our current knowledge by examining the specific associations among attachment, romantic relationship dysfunction, and BPD, above and beyond the contribution of emotional distress and nonromantic interpersonal functioning in two distinct samples. Study 1 comprised a community sample of women (N = 58) aged 25–36. Study 2 consisted of a psychiatric sample (N = 138) aged 21–60. Results from both Study 1 and Study 2 demonstrated that (1) attachment was specifically related to BPD symptoms and romantic dysfunction, (2) BPD symptoms were specifically associated with romantic dysfunction, and (3) the association between attachment and romantic dysfunction was statistically mediated by BPD symptoms. The findings support specific associations among attachment, BPD symptoms, and romantic dysfunction.